KONSEP FILSAFAT ILMU DALAM AL-QUR'AN - Fakhruddin, Fakhruddin (ULUL ALBAB Jurnal Studi Islam, 2007)
The Qur' an is the guide book for Muslims, not the scientific or philosophical book. It shows the right paths for the people who want _to succeed in their life in both this world and the hereafter. One of the content of the Qur'an is about the philosophy of science. This article describes the concept of the philosophy of science. It will elaborate the relationship between the philosophy and the philosophy of science in the beginning, and then the following part is the philosophy of science in the Qur'an. The discussion of the philosophy of science is always related to the matter of ontology, epistemology and axiology. The ontological aspect in the perspective of the scientific philosophy explains the essence of science. The epistemological aspect shows the ways to collect the knowledge, for instance, through the experience and thought. Finally, the axiological aspect discusses the way to implement the science in daily life, whether it is valuable or value free. The Qur'an since its first revelation of al-Alaq:1-5 has stated that science is very essential, some of them are developed by hard working (kasbi) or just given by God (ladunni). In addition, the Qur' an explains that the science can be achieved by the role of senses, brain, or intuition. Nevertheless, it is stated that the science is not value free. The science should be applied through the regulations which have been determined by the owner of science, the Almighty God, Allah.